2021
DOI: 10.1111/modl.12693
|View full text |Cite
|
Sign up to set email alerts
|

A Control–Value Theory Approach to Boredom in English Classes Among University Students in China

Abstract: There is a growing research interest in a variety of emotions in foreign and second language (L2) classrooms, especially since the introduction of positive psychology. However, research on the ubiquitous emotional experience of boredom is scant. Building on its prevalence and documented deleterious effects, I argue that research on the antecedents for the instigation of boredom is needed. Based on the control-value theory (CVT) of achievement emotions in educational psychology, this study took a mixed methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(146 citation statements)
references
References 42 publications
(100 reference statements)
6
102
0
Order By: Relevance
“…More specifically, according to the three-dimension taxonomy of the CVT (Pekrun, 2006), boredom and enjoyment share the two dimensions of the object focus as well as control, that is, they both arise from controllable ongoing activities. The dimension differentiates the value; that is, enjoyment is perceived as an emotion of positive quality while boredom has a negative quality (Li, 2021). Thus, the significant and negative relationships between them might be indicative of their conceptual characteristics and empirically support the CVT in an L2 context.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…More specifically, according to the three-dimension taxonomy of the CVT (Pekrun, 2006), boredom and enjoyment share the two dimensions of the object focus as well as control, that is, they both arise from controllable ongoing activities. The dimension differentiates the value; that is, enjoyment is perceived as an emotion of positive quality while boredom has a negative quality (Li, 2021). Thus, the significant and negative relationships between them might be indicative of their conceptual characteristics and empirically support the CVT in an L2 context.…”
Section: Discussionmentioning
confidence: 95%
“…The results showed that enjoyment and anxiety were related to learners' confidence, interest, motivation, engagement, cognition (e.g., attention), and finally to their overall English achievement. Li (2021) found that appraisals of perceived control and value negatively predicted boredom, uniquely or interactively, among 2002 Chinese EFL learners. Students who felt more proficient in English and valued their learning more reported feeling less bored, and vice versa.…”
Section: Control-value Theorymentioning
confidence: 92%
See 1 more Smart Citation
“…Under the influence of Pekrun's control-value theory of achievement emotion (Pekrun, 2006) as a second inspiring theory for researching emotions in SLA, positive emotions like enjoyment are seen emerging from the learning activities. Li (2021) maintained that the two influential theories of pp in SLA, namely, Fredrickson (2001) and Pekrun (2006) acknowledge the pivotal role of positive emotions in students' well-being and performance.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…The control-value theory of achievement emotions (Pekrun, 2006 ; Tulis and Fulmer, 2013 ; Li, 2021 ) asserts if no value is found through the completion of a task, then the students are obliged to implement it whether they like it or not, hence, they are more likely to see boredom emerging with its avoidance behaviors. To put it simply, students feeling more valued and competent are less likely to feel bored.…”
Section: Introductionmentioning
confidence: 99%